Practical and Academic Aspects of Social Work Development in Lithuania - Bagdonas, Albinas (Socialinė teorija, empirija, politika ir praktika, 2001)
The main objective of the article is to present the development of social work in Lithuania. The conception of social work and the social work definition problems are discussed in the first part. The absence of general social work theory and multfifunctionality of social work practice are obstacles for the unified conception of social work. The development of social work profession is discussed in the second part of the article. The roots of social work are the pseudoaltruistic behavior of animals and the proper altruistic behavior of hominids. There are eight stages of social work development in Lithuania according to author: GDL and the Union with Poland, period of Tsarist occupation, interwar independence, Models of Soviet social security, Formal acceptance of the notion of social work, professionalisation of social work, professional social work, social euro-integration. The contextual factors of social work in Lithuania are discussed in the third part of the article. The main contextual factors of social work are: socio-economical situation, legislative basis, international context, social service givers. The research in social work and the future development of social work discipline in Lithuania is discussed in the last part.
Keywords: Social work; Profession; Academic discipline; Case study; Lithuania